Model Discovery Learning Pada Pembelajaran Matematika Sekolah Menengah Pertama: A Bibliometric Review - Ilham Muhammad; Dadang Juandi (Universitas Negeri Gorontalo, 2023)
In the context of learning mathematics, the Discovery Learning method provides an effective approach to developing students' understanding and mathematical skills at the junior high school level. There have been many studies related to Discovery Learning. This study aims to determine the focus of research related to Discovery Learning in mathematics learning, especially at the junior high school level and its novelty. The method used is descriptive bibliometric analysis. A total of 21 data were taken from the Scopus database which had been refined with 4 stages (identification, screening, eligibility, and inclusion). The results showed that the number of publications related to this field reached its highest peak in 2017 and 2019. The publications made in 2017 had a significant influence on research related to Discovery Learning in mathematics learning in junior high schools. The Indonesian University of Education and Sebelas Maret University have a great influence in publications related to this field. The research focus related to Discovery Learning in mathematics learning is divided into two parts, namely, 1) educational computing, problem based learning, problem solving and self regulated learning; 2) geometry, and self-efficacy . New themes and novelty of research related to this context have been discussed in this article.